Environmental Cadmium Exposure Promotes the Development, Progression and Chemoradioresistance of Esophageal Squamous Cell Carcinoma - Chen, Jiongyu; Zhou, Zhangzhu; Lin, Xueqiong; Liao, Jiahui; Zhang, Yujie; Xie, Bingmeng; Huang, Yiteng; Peng, Lin (Frontiers in Cell and Developmental Biology, 2022)
Cadmium (Cd) exposure has been implicated in the etiology of esophageal squamous cell carcinoma (ESCC), , albeit with inconsistent results from epidemiologic studies and without causal evidence. In this study, we explore the relationship of cadmium exposure and the development, progression and therapeutic resistance of ESCC. A total of 150 ESCC patients and 177 matched controls from a coastal region with a high incidence of ESCC in China were included in the study. It was found that the median blood cadmium level (BCL) was significantly higher in ESCC patients than that in the controls. Odds ratios for ESCC risk were 3.12 (95% CI 1.54-6.30) and 3.71 (95% CI 1.84-7.48) in the third and fourth quartiles of Cd distribution, respectively. Notably, BCL above 4.71 µg/L was strongly associated with shorter progression-free survival time compared to that below 1.60 µg/L (P < 0.001). The chronic cadmium-treated ESCC cells (CCT-ESCC) CCT-EC109 and CCT-EC9706 exhibited increased cell proliferation and tumorigenesis, enhanced migration and invasion, and upregulated EMT biomarkers following 12 weeks of exposure to 5 μM cadmium chloride. Furthermore, cadmium treatment attenuated the efficacy of 5-fluorouracil, cisplatin and irradiation treatment in CCT-ESCC cells both in vitro and in vivo. Moreover, we revealed that cadmium stimulated the cancer cell stemness and Wnt/β-catenin signaling pathway in the CCT-ESCC cells. Treatment of CCT-ESCC cells with 5-aza-2-deoxy-cytidine suppressed the Wnt/β-catenin signaling pathway and restored the sensitivity to radiation treatment. These results offer new insights into the role of environmental cadmium exposure in the development, progression and chemoradioresistance of ESCC.